The Influence of Organizational Culture and Compensation on Employee Performance with Employee Motivation as an Intervening Variable at PT. Arai Rubber Seal Indonesia (ARSI) - Fiolita, Ata; Safaria, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of the research is to analyze the impact of organizational culture on employee performance, the impact of compensation on employee performance, the impact of motivation on employee performance, the impact of organizational culture, compensation through motivation on employee performance. PT Arai Rubber Seal Indonesia (ARSI). This research was composed using a quantitative approach. The research population is employees at PT. ARSI using proportional random sampling technique of 112 employees. Testing using SEM Smart PLS 3.0 The results Motivation has a significant impact on performance. Organizational culture has a significant impact on motivation, compensation has a significant impact on motivation, compensation has no significant impact on performance, organizational culture has a significant impact on performance. Compensation has no significant impact on performance through motivation as intervening variable. Furthermore, organizational culture has significant impact on performance through motivation as an intervening variable